Comparison of transoral endoscopic thyroidectomy vestibular approach and open conventional thyroidectomy regardıng inflammatory responses, pain, and patient satisfaction: a prospective study - Ünlü, Mehmet Taner; Aygun, Nurcihan; Serin, Erdinc; Uludag, Mehmet (Frontiers in Surgery, 2023)
Introduction: The application of transoral endoscopic thyroidectomy vestibular approach (TOETVA) is becoming widespread throughout the world. We primarily aimed to evaluate the severity of surgical trauma in TOETVA and open conventional thyroidectomy (COT) regarding the inflammatuar response including the comparison of surgical stress markers (IL-6, CRP, WBC). Material and Method: This non-randomised prospective study enrolled 2 groups including 20 patients in each; COT group and TOETVA group. Patients of 18-65 years with benign thyroid disease, with fine needle aspiration biopsy (FNAB) results of Bethesta III, IV or Bethesta V, VI (<1 cm nodule), thyroid volume <50 cm3, nodule diameter <4 cm, female gender without a previous neck, chin and/or oral surgery, without vocal cord paralysis (VCP) preoperatively, patients in euthyroid state were enrolled to the study. Preoperative, postoperative 2nd hour, 1st day and 2nd day CRP, WBC and IL-6 levels were evaluated. Pain intensity was evaluated with the Visual Analogue Scale (VAS) score on the 2nd and 12th hour, 1st and 2nd days postoperatively. Results: All the patients were female and mean age was significantly higher in COT group. The operative time was significantly longer in TOETVA group. No significant difference was found between the two groups regarding IL6 levels. In TOETVA group, postoperative 2nd hour WBC value (p=0.044), 1st (p=0.002) and 2nd day (p=0.005) CRP values were significantly higher. In TOETVA group, the lower lip and lower chin VAS scores were significantly higher at 2nd hour, 12th hour, on the 1st and 2nd days. The anterior neck VAS score was significantly higher in TOETVA group at the 2nd hour (p=0.025). General and cosmetic satisfaction were similar at 15th and 30th days in both groups. Conclusion: The longer operative time, higher postoperative CRP level and VAS score in the chin and lower lip in the TOETVA group suggest that the method is not a minimally invasive technique compared to COT. However, presence of similar total complication rates and early postoperative general and aesthetic satisfaction which improves over time in both of the groups suggests that the clinical effect of increased magnitude of SIR in TOETVA might be temporary and acceptable.